Species‐specific DNA distribution in spruce–beech forest soil - Alessandro Foscari; Giorgio Alberti; Maurizio Zotti; Guido Incerti (Environmental DNA, 2022)
Abstract Environmental DNA consists of species‐specific intracellular and extracellular fractions, whose content and information may not be similar in all environments. In forest soil, in particular, the biogeochemical fate of DNA originated by plant litter input has been extensively reviewed, but species‐specific persistence and distribution still await to be quantified. In the present work, based on the purification of extracellular and intracellular DNA fractions from forest soil samples representing 3 soil horizons at 36 randomized locations differing for stand composition (either beech‐ or spruce‐dominated, and mixed), followed by exDNA metabarcoding with the rbcL marker, we provide a clear picture of species‐specific plant DNA distribution, and explore plant community composition and diversity along the explored gradient and the soil profile. We did not find significant differences in intra‐ vs. extracellular total DNA distribution, with a progressive depletion with soil depth positively associated with soil organic C and N content and negatively associated with soil pH and mineral content. Species‐specific DNA distribution was horizontally dependent on beech and spruce basal area aboveground, while extracellular DNA showed peculiar species‐specific vertical patterns. Proportion of Fagus sylvatica DNA increased with depth in beech stand soil, and Picea abies DNA decreased in spruce stand soil, respectively, possibly linked to species‐specific differences in leaf litter decomposition dynamics and root litter contributions. Finally, our approach by metabarcoding provided a faithful, although incomplete, picture of the local plant diversity, suggesting that such technique could positively integrate traditional biodiversity inventory studies based on expert field assessments.